PELAYANAN PROGRAM DISDUKCAPIL ONLINE DALAM PENERBITAN KARTU IDENTITAS ANAK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BANJARMASIN PROVINSI KALIMANTAN SELATAN - Dony Dwi Harsono (Jurnal Teknologi dan Komunikasi Pemerintahan, 2022)
The purpose of the research is to find out how the Online Disdukcapil program services in the Issuance of Children's Identity Cards in the Banjarmasin City Population and Civil Registration Office. This study uses qualitative descriptive methods. The results showed that the Population and Civil Registration Office of Banjarmasin city had carried out public services according to service standards in the manufacture of KIA, where the service was carried out online using the WhatsApp (WA) application via android phone, the cost incurred was only ten thousand rupiah to pay for postal courier services that would deliver KIA to the applicant who made it. The provision of facilities and infrastructure has been adequate in accordance with the Covid-19 health protocol, and place competent officers so as to facilitate in the provision of services. In the results of this study, many people still do not know and understand about this service and socialization is needed how this service should be obtained by the community. Lack of interest in parents to register for KIA, the absence of sanctions rules from the government or sanctions written in the policy for the community, especially parents whose children do not have a kia even though kia is required, there is still a lack of cooperation with business partnerships In addition there are also some technical obstacles, especially from the internet network and not all people have android phones and understand the mechanism of online services. Keywords: Online Service, Child Identity Card, Population Office and Civil Registration